Linkage analysis identifies an isolated strabismus locus at 14q12 overlapping with FOXG1 syndrome region. Issue 1 (30th November 2020) - Ye, Xin (Cynthia); Roslin, Nicole M; Paterson, Andrew D; Lyons, Christopher J; Pegado, Victor; Richmond, Phillip; Shyr, Casper; Fornes, Oriol; Han, XiaoHua; Higginson, Michelle; Ross, Colin J; Giaschi, Deborah; et al.
Abstract : Strabismus is a common condition, affecting 1%–4% of individuals. Isolated strabismus has been studied in families with Mendelian inheritance patterns. Despite the identification of multiple loci via linkage analyses, no specific genes have been identified from these studies. The current study is based on a seven-generation family with isolated strabismus inherited in an autosomal dominant manner. A total of 13 individuals from a common ancestor have been included for linkage analysis. Among these, nine are affected and four are unaffected. A single linkage signal has been identified at an 8.5 Mb region of chromosome 14q12 with a multipoint LOD (logarithm of the odds) score of 4.69. Disruption of this locus is known to cause FOXG1 syndrome (or congenital Rett syndrome; OMIM #613454 and *164874), in which 84% of affected individuals present with strabismus. With the incorporation of next-generation sequencing and in-depth bioinformatic analyses, a 4 bp non-coding deletion was prioritised as the top candidate for the observed strabismus phenotype. The deletion is predicted to disrupt regulation of FOXG1, which encodes a transcription factor of the Forkhead family. Suggestive of an autoregulation effect, the disrupted sequence matches the consensus FOXG1 and Forkhead family transcription factor binding site and has been observed in previous ChIP-seq studies to be bound by Foxg1 in early mouse brain development. Future study of this specific deletion may shed light on the regulation of FOXG1 expression and may enhance our understanding of the mechanisms contributing to strabismus and FOXG1 syndrome.